Rancang Bangun Sistem Monitoring Pada Bendungan Dengan Menggunakan Metode Fuzzy Tahani Berbasis Mikrokontroler - Hengki Sikumbang; Indrianto Indrianto; Garang Syahputra Siregar (PETIR, 2021)
This research designed a monitoring system on dam by using fuzzy tahani method based on Microcontroller. This tool is designed to be used as monitoring on the Katulampa Dam. This tool consists of Raspberry module Pi 3 model B, ultrasonic sensors, resistors and android. The monitoring system on the dam is used to inform the user/citizen when the water in the dam has exceeded the specified height limit and notify the user of the appliance if there is a possibility of flooding, so that residents around the dam can be alert and avoid danger caused by flood . So that with the tool is expected to provide solutions to residents around the dam and residents whose homes are near the dam river flow in case of sudden danger or flood within 24 hours in real time and can minimize casualties due to flooding. By using application module on android that can give notification sms to appliance user and citizen, hence citizen around the dam will be more secure and protected from danger caused by flood and can minimize victim or other loss caused by flood.